A work in progress—after 35 years of nursing. (2nd February 2021) - Millerick, Yvonne
Abstract : As a nominee for the new 2020 British Society for Heart Failure Lynda Blue Award, Yvonne Millerick sheds some light on her nursing career and her work in cardiac palliative care in our 2021 Spotlight on Nurses series.